2017
DOI: 10.1016/j.bbmt.2017.05.026
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Role of Low-Dose Antithymocyte Globulin in Unrelated Stem Cell Transplantation for Adult Patients with Acquired Severe Aplastic Anemia: Reduction of Graft-versus-Host Disease and Improvement of Graft-versus-Host Disease–Free, Failure-Free Survival Rate

Abstract: Stem cell transplantation (SCT) from an unrelated donor (URD) is often considered in patients with severe aplastic anemia (SAA) whom immunosuppressive therapy failed and matched sibling donor is not available. To reduce the incidence of graft-versus-host disease (GVHD) in URD SCT, introducting antithymocyte globulin (ATG) into the conditioning regimen has been proposed. Although ATG was shown to play a role in reducing GVHD in a cohort with diverse hematologic diseases, its role in SAA remains uncertain. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
3
13
1
Order By: Relevance
“…However, the incidence of chronic GVHD was relatively high. Park et al reported that the administration of ATG from day −3 to −2 at a dose of 1.25 mg/kg/day prevented chronic GVHD at a percentage of 21.9% . This was in HSCT from an unrelated donor for patients with AA, which was lower than the incidence in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…However, the incidence of chronic GVHD was relatively high. Park et al reported that the administration of ATG from day −3 to −2 at a dose of 1.25 mg/kg/day prevented chronic GVHD at a percentage of 21.9% . This was in HSCT from an unrelated donor for patients with AA, which was lower than the incidence in our study.…”
Section: Discussioncontrasting
confidence: 68%
“…TBI‐600 cGy/Flu/intermediate‐dose ATG resulted in feasible outcomes of Haplo‐SCT for adult patients with SAA, indicated by the 91.7% OS and 78.4% GFFS rates. These outcomes were comparable to those of URD‐SCT reported in our previous study . In URD‐SCT for adult patients with SAA, OS, and GFFS rates were approximately 84.0%‐92.3% and 30.8%‐62.5% according to the use of ATG, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…We previously reported early results from a pilot prospective study to determine the dose of TBI to be used in combination with 120 mg/kg of Cy as a conditioning regimen for URD‐SCT in adult patients with SAA, which demonstrated the superiority of 800 cGy of TBI compared to higher doses of TBI (1000 and 1200 cGy) . Later, we extended our experience, showing the feasibility of 800 cGy of TBI in combination with 120 mg/kg of Cy with engraftment of all patients . A TBI dose de‐escalation strategy for reducing transplant‐related toxicity without jeopardizing engraftment has also been reported …”
Section: Discussionmentioning
confidence: 92%
“…In our study, all patients with AA received an ATG-based conditioning regimen, and GVHD prophylaxis consisted of CsA, mycophenolate mofetil, and low-dose methotrexate. Compared with a patient population treated with URD HSCT with total body irradiation and CY as the preparative regimen (grade II-IV aGVHD, 46%; cGVHD, 50%) [34], our URD patients had a 21.7% CI of aGVHD (no patients developed grade III-IV aGVHD) and a, 18.2% CI of cGVHD, and the use of ATG contributed to this low incidence [35,36]. A small number of pediatric AA patients underwent first-line URD transplantation, and the rate of GVHD was low with the alemtuzumab-based regimen (Flu + Cy + alemtuzumab) [12].…”
Section: Discussionmentioning
confidence: 75%